SWIMMING SPEED KAPIEK FISH (Barbodes schwanenfeldii) IN CURRENT TANK (FLUME TANK) USING CURRENT AND IN AQUARIUM WITHOUT CURRENT - Safitri, Gita Nur; Nofrizal, Nofrizal; Syaifuddin, Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThis Research was conducted on 15-30 Mei 2021 in the Laboratory of Fishing Gear Materials of Faculty of Fisheries and Marine, University of Riau. The method that used in this research was experiment method in laboratory by testing directly to the samples, the number of the samples used were 30 fish with 9-12 cm overall body length (average of 9,00 cm) with standard deviation ± 0,6977 cm. The testing results show that the normal swimming speed of kapiek fish (sustained swimming speed)< 3,21FL/sec. Maximum sustained swimming speed is 3,21 FL/sec, Prolonged swimming speedof kapiek fish range from 3,21 – 11,66FL/sec, burst swimming speed11,66FL/sec. Swimming speed and swimming endurance of kapiek fish (Barbodes schwanenfeldii) has negative correlation with strong value (R2 = 0,3415). Based on the results it proves that the endurance of fish swimming will decrease at high swimming speeds, in otherwise if the swimming speed is high, the endurance of swimming will decrease.The swimming speed of fish in the flume tank is 14,82 FL/second while the swimming speed of fish in aquaerium is not up to 14 FL/second. So it shows that the swimming speed of fish in the aquarium is lower or below the flume tank.Key word : Swimming Speed, Swimming Endurance, Kapiek fish